PERANCANGAN TEKNIK SULAM KRUISTIK SEBAGAI HIASAN PADA KELAMBU TEMPAT TIDUR BAYI - Fadiyah, Fadiyah (Narada : Jurnal Desain dan Seni, 2022)
Currently the use of mosquito nets is mostly replaced by using mosquito repellents with modern electronic devices that are filled with liquid. However, excessive use of chemicals is very bad for the health of the body in long term. This is makes the author have the idea to design a baby mosquito net by add a cross stitch technique in creating a motif on the fabric surface design so that the mosquito net in addition to protecting it self from mosquito bites, the mosquito net can also be a decorative in the room because of the motifs made using cross stitch techniques. The design of mosquito net product is carried out using the application theory of SP. Gustami in creating craft art there are three stages, the exploration stage which includes the search for ideas and data for the initial design, the design stage includes data analysis as a reference in making the work, and the embodiment stage includes the final result of the work. The cross embroidery technique was chosen as a way to apply the motif, which has been considered from how the structure of the perforated tille fabric. The advantages of using the technique of cross embroidery, the resulting motif are more neat and orderly, the shapes and colors that are expected from the beginning of the design can be realized ad expected.